BRM polymorphisms, pancreatic cancer risk and survival. Issue 11 (18th August 2016) - Segedi, Maja; Anderson, Laura N.; Espin‐Garcia, Osvaldo; Borgida, Ayelet; Bianco, Teresa; Cheng, Dangxiao; Chen, Zhuo; Patel, Devalben; Brown, M. Catherine; Xu, Wei; Reisman, David; Gallinger, Steven; et al.
Abstract : Variant alleles of two promoter polymorphisms in the BRM gene (BRM‐741, BRM‐1321), create MEF2D transcription binding sites that lead to epigenetic silencing of BRM, the key catalytic component of the SWI/SNF chromatin remodeling complex. BRM suppression can be reversed pharmacologically. 1 Our group and others have reported associations with lung, head and neck, hepatocellular cancer risk, 1–3 and with lung and esophageal cancer prognosis (ASCO 2013; abstract 11057 & 4077). Herein, we assessed risk and survival associations with pancreatic cancer. A provincial population‐based case‐control study was conducted with 623 histologically confirmed pancreatic adenocarcinoma cases and 1, 192 age/gender distribution‐matched controls. 4 Survival of cases was obtained through the Ontario Cancer Registry. Logistic and Cox proportional hazard regression models were fitted, adjusting for relevant covariates. Median age was 65 y; 52% were male; Stage I (8%), II (55%), III (14%), IV (23%); 53% after curative resection, 79% after chemotherapy; and 83% had died. In the risk analysis, adjusted odds ratios (aOR) were 1.01 (95% CI: 0.1–2.0) and 0.96 (95% CI: 0.7–1.3) for the homozygotes of BRM‐741 and BRM‐1321, respectively; aOR of double‐homozygotes was 1.11 (95% CI: 0.80–1.53), compared to the double‐wildtype. For the survival analysis, adjusted hazard ratios (aHR) were 2.19 (95% CI: 1.9–2.5) for BRM‐741 and 1.94 (95% CI: 1.7–2.2) for BRM‐1321, per unit increase in variant alleles. Compared with the double‐wildtype, aHR for carrying no, one, and two double‐homozygotes were 2.14 (95% CI: 1.6–2.8), 4.17 (95% CI: 3.0–5.7), 8.03 (95% CI: 5.7–11.4), respectively. In conclusion, two functional promoter BRM polymorphisms were not associated with pancreatic adenocarcinoma risk, but are strongly associated with survival. Abstract : What's new? The putative tumor suppressor gene BRM is inactivated in about 20% of solid tumor types, with its silencing occurring through epigenetic alterations of two variants in the promoter region. In this study, the influence of those variants on risk and survival in cancer was explored in more than 620 patients with pancreatic adenocarcinoma. Analyses show that the two polymorphisms, BRM‐741 and BRM‐1321, are significantly associated with worse survival but not with increased risk of developing pancreatic cancer. The findings are of potential therapeutic importance, as BRM silencing is pharmacologically reversible.